Aminophenol isomers unraveled by conformer-specific far-IR action spectroscopy. Issue 8 (8th February 2016) - Yatsyna, Vasyl; Bakker, Daniël J.; Feifel, Raimund; Rijs, Anouk M.; Zhaunerchyk, Vitali
Abstract : Far-infrared action spectroscopy of aminophenol in the gas-phase revealed isomer- and conformer-specific vibrational signatures and provided the heights of NH2 inversion barrier. Abstract : Spectroscopic studies of molecular structure can strongly benefit from extending the conventional mid-IR range to the far-IR and THz regions, as low-frequency molecular vibrations provide unique fingerprints and high sensitivity to intra- and intermolecular interactions. In this work, the gas-phase conformer specific far-IR spectra of aminophenol isomers, recorded in the spectral range of 220–800 cm −1 at the free-electron laser laboratory FELIX in Nijmegen (the Netherlands), are reported. Many distinct far-IR vibrational signatures which are specific for the molecular structure of the different aminophenol isomers are revealed and assigned. The observed far-IR transitions of the NH2 wagging (inversion) motion have been treated with a double-minimum harmonic well potential model that has enabled us to obtain the inversion barrier values. Moreover, we discuss the limitations and capability of conventional DFT frequency calculations to describe the far-IR vibrational modes.